2010
DOI: 10.3767/003158510x550845
|View full text |Cite
|
Sign up to set email alerts
|

<I>Ophiostoma</I> spp. associated with pine- and spruce-infesting bark beetles in Finland and Russia

Abstract: The timber and pulp industries of Finland rely heavily on importations from Russia as source of raw timber. These imports raise the risk of accidentally importing forest pests and pathogens, especially bark beetles and their associated fungi, into Finland. Although ophiostomatoid fungi have previously been reported from Finland and Russia, the risks of accidentally moving these fungi has prompted a first survey to compare the diversity of conifer-infesting bark beetles and associated fungi from boreal forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(103 citation statements)
references
References 85 publications
8
94
1
Order By: Relevance
“…Based on CAL data, O. noisomeae formed a distinct clade, but its affinities are unclear as CAL data of S. lignivora and Graphilbum species are still lacking. Our analyses support results of De Beer et al (2013b) and Linnakoski et al (2010) that the S. lignivora complex and O. noisomeae form distinct lineages with significant distance from other genera and complexes in the Ophiostomatales. De Beer et al (2013b) suggested that, due to the distance at which the S. lignivora complex groups from other complexes and genera in the Ophiostomatales, the group may represent a separate genus.…”
Section: Discussionsupporting
confidence: 91%
“…Based on CAL data, O. noisomeae formed a distinct clade, but its affinities are unclear as CAL data of S. lignivora and Graphilbum species are still lacking. Our analyses support results of De Beer et al (2013b) and Linnakoski et al (2010) that the S. lignivora complex and O. noisomeae form distinct lineages with significant distance from other genera and complexes in the Ophiostomatales. De Beer et al (2013b) suggested that, due to the distance at which the S. lignivora complex groups from other complexes and genera in the Ophiostomatales, the group may represent a separate genus.…”
Section: Discussionsupporting
confidence: 91%
“…It appears that the fungus has a relatively specific association with this bark beetle species and its host tree. This apparently strict association has also been reported in several previous studies (Mathiesen 1950(Mathiesen , 1951Rennerfelt 1950;Mathiesen-Käärik 1953;Francke-Grosmann 1952, 1963aKäärik 1975aKäärik , 1980Villari 2012;Villari et al 2013 1989, 1991Kirisits et al 2000;Kirisits 2001Kirisits , 2004Bueno et al 2010;Stauffer et al 2001;Jankowiak et al 2007Jankowiak et al , 2009Linnakoski et al 2010;Linnakoski 2011;Jankowiak 2012;Repe et al 2013). For this reason, we re-examined some isolates from our previous studies identified as O. brunneo-ciliatum (Linnakoski et al 2010;Linnakoski 2011;Villari et al 2013 clavatum complex.…”
Section: Ipssupporting
confidence: 51%
“…Descriptions: Solheim (1986, p. 201 Original reports in literature: Solheim (1986Solheim ( , 1992Solheim ( , 1993; Harding (1989); Pashenova et al (1995); Yamaoka et al (1997); Grubelnik (1998);Viiri (1997); Kirschner (1998Kirschner ( , 2001 (Linnakoski et al 2010;Repe et al 2013). Reports of this species from larch-and pine-infesting bark beetles will, therefore, require confirmation, as they may refer to other members in the O. clavatum species complex.…”
Section: Morphological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bark beetles that infest conifers carry many different ophiostomatoid fungi including those related to Ophiostoma (Jacobs and Kirisits 2003;Kim et al 2003;Zhou et al 2004Zhou et al , 2006Kirisits 2007;Romon et al 2007;Linnakoski et al 2008Linnakoski et al , 2009Masuya et al 2009;Jankowiak and Kolarik 2010;Linnakoski et al 2010;Paciura et al 2010) and Ceratocystis (Harrington and Wingfield 1998, Harrington et al 2002, van Wyk et al 2004, Viiri and Lieutier 2004, Reid et al 2010. Although many of these fungi have the ability to cause lesions when inoculated into conifers (e.g.…”
Section: Introductionmentioning
confidence: 99%